EPS Memediasi Pengaruh ROE Terhadap Return Saham LQ45 Periode 2019-2024 - Nicholas Oktavianus; Faradila Meirisa (MDP Student Conference, 2026)
Abstract: This study aims to analyze and explain the effect of Return on Equity (ROE) on Stock Returns with Earning Per Share (EPS) as an intervening variable in companies listed in the LQ45 index during the period 2019-2024. The research population includes 73 companies, with a purposive sampling technique resulting in 28 sample companies (168 observations). The data analysis method uses path analysis and Sobel test assisted by IBM SPSS 26. The results of the study indicate that partially, ROE has a positive and significant effect on both EPS and Stock Returns. However, it was found that EPS does not have a significant effect on Stock Returns. The mediation test results using the Sobel test show that EPS is unable to mediate the effect of ROE on Stock Returns, because the direct effect value is much greater than the indirect effect. This indicates that investors in liquid stocks (LQ45) are more likely to respond directly to equity profitability performance than to earnings per share information in determining their expected returns.